Electrical characterization of mixed conducting SCY-YDC composite electrolyte. Issue 10 (July 2020) - Luo, Yadan; Li, Ying; Li, Min
Abstract: SrCe0.9 Y0.1 O3-δ -Ce0.9 Y0.1 O2-δ (SCY-YDC, 1:1 mole ratio), as a novel composite electrolyte, was successfully synthesized and characterized. X-ray diffraction patterns showed that SCY-YDC composite electrolyte is a mixture of SCY and YDC. Besides, no impurity phase emerged after sintering at 1550 °C for 10 h. AC impedance spectroscopy was used to determine the electrical properties of SCY-YDC at 500–800 °C in various atmospheres. Partial conductivities of oxygen vacancies, protons, and electrons (p-type) were calculated using the defect structure model. Results showed that SCY-YDC is a mixed (hole, proton, and oxygen-ion) conductor. Moreover, the contribution of holes is minor at 650–800 °C in high pressure (1 atm) or low pressure (10 −4  atm) O2 atmospheres. Dominant carrier switched from protons to oxygen ions as temperature increased at vapor pressure in air of 0.038 atm. Total conductivity for SCY-YDC is 6.19 × 10 −3  S cm −1 at 800 °C under pO2  = 1 atm and pH2 O = 6 × 10 −3  atm, which is higher than that of SCY (2.47 × 10 −3  S cm −1 ). Results also showed that SCY-YDC composite material exhibits higher ionic conductivity and lower electron-hole conductivity than SCY. Electron-hole transference number for SCY-YDC is 0.049 at 800 °C in pO2  = 0.21 atm and pH2 O = 0.038 atm. Ultraviolet–visible spectrophotometry results provided evidence that SCY-YDC can suppress electron conduction.